2016
DOI: 10.1038/srep26622
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of in ovo treatment with the chicken cathelicidin analog D-CATH-2 against avian pathogenic E. coli

Abstract: Increasing antibiotic resistance and ever stricter control on antibiotic use are a driving force to develop alternatives to antibiotics. One such strategy is the use of multifunctional Host Defense Peptides. Here we examined the protective effect of prophylactic treatment with the D analog of chicken cathelicidin-2 (D-CATH-2) against a respiratory E. coli infection. Chickens were treated with D-CATH-2 in ovo at day 18 of embryonic development or intramuscularly at days 1 and 4 after hatch. At 7 days of age, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 46 publications
(58 reference statements)
1
44
0
Order By: Relevance
“…Results revealed that prophylactic treatment of chickens with D‐CATH‐2 on day 18 of embryonic development through the in ovo method significantly reduced morbidity (63%) and respiratory bacterial load of avian pathogenic E. coli . Such findings support the assumption that the rational use of host defense peptide‐derived D‐CATH‐2 can be a suitable alternative to antibiotics in the poultry sector when used by the in ovo route …”
Section: Applications Of In Ovo Technology For Various Biological Supsupporting
confidence: 78%
See 1 more Smart Citation
“…Results revealed that prophylactic treatment of chickens with D‐CATH‐2 on day 18 of embryonic development through the in ovo method significantly reduced morbidity (63%) and respiratory bacterial load of avian pathogenic E. coli . Such findings support the assumption that the rational use of host defense peptide‐derived D‐CATH‐2 can be a suitable alternative to antibiotics in the poultry sector when used by the in ovo route …”
Section: Applications Of In Ovo Technology For Various Biological Supsupporting
confidence: 78%
“…Such findings support the assumption that the rational use of host defense peptide-derived D-CATH-2 can be a suitable alternative to antibiotics in the poultry sector when used by the in ovo route. 163,164 The in ovo route is also used by researchers to assess any toxicity produced by commercially available insecticides; namely, chlorpyrifos, cypermethrin, and spinosad during the development stage in fertilized eggs of Rhode Island Red chickens. Pesticides have been administered via in ovo in a single dose in different concentrations and combinations.…”
Section: Vaccines and Drugsmentioning
confidence: 99%
“…Additive transgenic expression of porcine cathelicidin PR-39 in normal mice ameliorates the infection’s necrotic phenotype [ 59 ]. In vivo treatment of 18-day-old fertilized chicken eggs with D-chCATH-2 protects chicks from avian Escherichia coli ( E. coli ) infections when they are challenged 7 days after hatching [ 60 ]. The amount of peptide still present in the organs at that time is sufficiently low to conclude that the anti-infective properties of chCATH-2 are likely derived from immunomodulation.…”
Section: Biological Functions Of Cathelicidinsmentioning
confidence: 99%
“…Besides having broad antibacterial activity, it can inhibit LPS-induced TLR4 activation and enhance DNA-induced TLR21 activation in macrophages (Coorens et al, 2015;Coorens et al, 2017). Furthermore, CATH-2 treatment in ovo has been described to reduce mortality induced by avian pathogenic E. coli in chicken (Cuperus et al, 2016). Less information is known about the other chicken cathelicidins.…”
Section: Introductionmentioning
confidence: 99%